Nervous system dysfunction in Henoch–Schönlein syndrome: systematic review of the literature - Garzoni, Luca; Vanoni, Federica; Rizzi, Mattia; Simonetti, Giacomo D.; Simonetti, Barbara Goeggel; Ramelli, Gian P.; Bianchetti, Mario G. (Rheumatology (Oxford, England), 2009)
Objective. CNS or peripheral nervous system dysfunction sometimes occurs in Henoch–Schönlein patients. Methods. We review all Henoch–Schönlein cases published after 1969 with CNS dysfunction without severe hypertension and neuroimaging studies (n = 35), cranial or peripheral neuropathy (n = 15), both CNS and peripheral nervous system dysfunction without severe hypertension (n = 2) or nervous system dysfunction with severe hypertension (n = 2). Forty-four of the 54 patients were <20 years of age. Results. In patients with CNS dysfunction without or with severe hypertension the following presentations were observed in decreasing order of frequency: altered level of consciousness, convulsions, focal neurological deficits, visual abnormalities and verbal disability. Imaging studies disclosed the following lesions: vascular lesions almost always involving two or more vessels, intracerebral haemorrhage, posterior subcortical oedema, diffuse brain oedema and thrombosis of the superior sagittal sinus. Following lesions were noted in the subjects with cranial or peripheral neuropathy without severe hypertension: peroneal neuropathy, peripheral facial palsy, Guillain–Barré syndrome, brachial plexopathy, posterior tibial nerve neuropathy, femoral neuropathy, ulnar neuropathy and mononeuritis multiplex. Persisting signs of either CNS (n = 9) or peripheral (n = 1) nervous system dysfunction were sometimes reported. Conclusions. In Henoch–Schönlein syndrome, signs of nervous system dysfunction are uncommon but clinically relevant. This review helps clinicians managing Henoch–Schönlein syndrome with nervous system dysfunction.